Study on yolk iron transportation in chick embryo eggs based on transcriptomics - Lulu Ma; Zhaowei Cui; Shuaishuai Wei; Jiaying Huo; Shijian Dong; Shugang Li (Poultry Science)
Chick embryo eggs have a complete system of iron release, delivery, and uptake and thus provide a useful tool to study the fast transportation and absorption of iron. Based on this, the regulatory genes and pathways of iron transportation and uptake at the four key stages of chick embryo incubation, days 6, 9, 12, and 15 (E6, E9, E12, and E15), were investigated. Throughout these four key stages, the iron content decreased in egg yolk, increased in chick embryos, and first increased and then decreased in the yolk sac membrane (YSM) with the highest value of 110.38 mg/kg at E12. A total of 87,499 expressed genes were detected by transcriptome, where the specifically expressed genes at E6, E9, E12, and E15 were 312, 466, 280, and 185 respectively. Mineral absorption pathways involved in mineral uptake, transportation, utilization, and metabolism were significantly enriched in stages E9 to E15. The expression of divalent metal transporter 1 (DMT1) and ferritin heavy chain 1 (FTH1) related to iron transportation was up-regulated considerably from E9 to E12. Heme oxygenase 1 (HMOX1), FTH1, Solute Carrier Family 40 Member 1 (SLC40A1), and hephaestin (HEPH) mainly responsible for the regulation of iron transportation and uptake were up-regulated from E12 to E15. Therefore, stage E9 to E12 was the crucial period for iron initiation and transportation, and DMT1 and FTH1 played an important role in regulating the initiation of iron transportation at the early stage of incubation.